1999
DOI: 10.1093/jjco/29.12.617
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reference Values for Total PSA, F/T and PSAD According to Prostatic Volume in Japanese Prostate Cancer Patients with Slightly Elevated Serum PSA Levels

Abstract: The reference values for total PSA, F/T and PSAD must be changed according to prostatic volume in order to maintain a sufficient diagnostic sensitivity of CAP. Of these parameters, PSAD showed a high specificity in the group with a prostatic volume of <40 ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…These results are in contrast to most other studies, which usually preferred PSAD cut-off levels near 0.15. 24,38,42 In another comparable study regarding the number of patients (n ϭ 1913 patients), Kuriyama et al 29 recommended different reference values for PSAD according to prostate volume. It can seen in Table 2 that our data confirm the lower PSAD values with increasing volume.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are in contrast to most other studies, which usually preferred PSAD cut-off levels near 0.15. 24,38,42 In another comparable study regarding the number of patients (n ϭ 1913 patients), Kuriyama et al 29 recommended different reference values for PSAD according to prostate volume. It can seen in Table 2 that our data confirm the lower PSAD values with increasing volume.…”
Section: Discussionmentioning
confidence: 99%
“…4 -9,35 To date, only 1 study has been performed in Ͼ 1000 men to verify the parameters PSA, PSAD, and %fPSA. 29 In 1913 Japanese men who had a tPSA from 2 ng/mL to 20 ng/mL, the specificity of all parameters was low for men who had prostate volumes Ͼ 40 mL but was better in men who had smaller glands (Ͻ 20 mL). 29 The authors of that report concluded that reference values for tPSA, %fPSA, and PSAD must be changed according to prostate volume.…”
mentioning
confidence: 97%
See 3 more Smart Citations